The Konse Group on the SE margin of the Tanzania Craton: a Paleoproterozoic passive margin succession of the Usagaran Orogen : constraints from metamorphic monazite ages and isotopically heavy carbon in marbles - Schenk, Volker; Bekker, Andrey; Schmitt, Axel Karl (Precambrian research, 2025)
The Konse Group is a 2-3 km thick succession of quartzites, metaconglomerates, micaschists, marbles, Mn-rich metasediments and mafic metavolcanics deposited over >200 km in a narrow basin along the SE margin of the Archean Tanzania Craton. The timing of basin formation with respect to the Paleoproterozoic Usagaran orogeny is controversial: it is interpreted either as post-orogenic, overlying folded Usagaran gneisses, or as pre-orogenic, developed on the craton margin. In the latter case, the Konse Group is regarded as a lower-grade, time equivalent of the tectonically overlying Usagaran gneisses, which represent the deeper part of the same basin. Nearly U-free monazite from oxidized Mn3+-rich Konse Group micaschists yielded a Th-Pb age of 2028 ± 15 Ma (95 % confidence) for metamorphism, which argues against a post-orogenic depositional age. The low U content and Mn3+-enrichment are attributed to oxidizing conditions in the precursor sediment. The pre-Usagaran depositional age is supported by highly positive δ13C values, +12.6 and +9.3 ‰, for marbles of the Konse Group and correlative Mpwapwa Group to the northeast, respectively, indicating sedimentation during the ca. 2.22-2.06 Ga Lomagundi Event. Both groups share a similar depositional age and tectonic setting with marginal successions of other southeastern African cratons, which were deposited at early stages during the assembly of the Paleoproterozoic Columbia/Nuna supercontinent. The Konse and Mpwapwa groups represent cratonic passive margin successions, which belong to the Usagaran Orogen. The latter contains essential lithological members of a Wilson cycle, suggesting that modern-style plate tectonics operated during the Paleoproterozoic.